Molecular study of blaVIM and blaIMP genes in Acinetobacter baumannii strains isolated from burn patients in Duhok City, Iraq - Haval Mohammed Khalid (Journal of Infection in Developing Countries)
Introduction: Acinetobacter baumannii (A. baumannii) is an opportunistic pathogenic bacterium mainly associated with hospital acquired infections and in immunocompromised individuals who stay in hospitals for a long time. In recent years, it has become increasingly resistant to many different types of antibiotics. The production of the metallo-beta-lactamase (MBL) enzyme is one of the primary causes of this resistance. This study aimed to detect the presence of MBL genes that belong to the verona integrin metallo-β-lactamase (bla-VIM) and imipenemase (bla-IMP) groups in the isolates of Acinetobacter baumannii from burn patients.